Effect of Extracellular Vesicles From Multiple Cells on Vascular Smooth Muscle Cells in Atherosclerosis - Li, Tong; Wang, Baofu; Ding, Hao; Chen, Shiqi; Cheng, Weiting; Li, Yang; Wu, Xiaoxiao; Wang, Lei; Jiang, Yangyang; Lu, Ziwen; Teng, Yu; Su, Sha; et al. (Frontiers in Pharmacology, 2022)
Abstract Atherosclerosis (AS)-related diseases are still the main cause of death in clinical patients. The phenotype switching, proliferation, migration, and secretion of vascular smooth muscle cells (VSMCs) have a pivotal role in atherosclerosis. Although numerous researches have elucidated the role of VSMCs in AS, their potential functional regulations continue to be explored. The formation of AS involves various of cells, such as endothelial cells, smooth muscle cells and macrophages. Therefore, intercellular communication can’t be ignored of blood vessels due to close-connected of endothelia, media and adventitia. Extracellular vesicles (EVs), as the vectors of cell-to-cell communication, can deliver protein and nucleic acids of parent cells to the recipient cells. EVs have emerged as being central in intercellular communication and play a vital role in the pathophysiologic mechanisms of AS. This review summarizes the effects of extracellular vesicles (EVs) derived from multiple cells (endothelial cells, macrophages, mesenchymal stem cells, etc.) on VSMCs in AS. The key findings of this review are: (1) endothelial cell-derived EVs (EEVs) have anti- or pro-atherogenic effects on VSMCs; (2) macrophage-derived EVs (MEVs) aggravate the proliferation and migration of VSMCs; (3) mesenchymal stem cells can inhibit VSMCs; (4) the proliferation and migration of VSMCs can be inhibited by the treatment of EVs with atherosclerotic protective factors and promoted by noxious stimulants. These results suggested that EVs have the same functional properties as treated parent cells, which might provide vital guidance for treating AS. Keywords: atherosclerosis, endothelial cells, extracellular vesicles, macrophages, vascular smooth muscle cells